Halothane Sensitizes the Guinea-Pig Heart to Pharmacological IKr Blockade: Comparison With Urethane Anesthesia - Yasue Sakaguchi; Atsushi Sugiyama; Shuji Takao; Yasuki Akie; Akira Takahara; Keitaro Hashimoto (Elsevier, 2005)
Potential utility of halothane-anesthetized guinea pigs for detecting drug-induced repolarization delay was analyzed in comparison with urethane-anesthesia (n = 4 for both groups). Basal QT interval was significantly greater under halothane-anesthesia than urethane-anesthesia (192 ± 7 vs 132 ± 5 ms, respectively), whereas the reverse was true for the heart rate (190 ± 7 vs 248 ± 11 beats/min, respectively). The typical IKr-blocker dl-sotalol (0.1 to 3mg/kg, i.v.) induced dose-related bradycardia and QT interval prolongation under each anesthesia. The extent of maximum prolongation in the QT interval was greater under halothane-anesthesia than urethane-anesthesia (+101 ± 15 vs +49 ± 3 ms, respectively), whereas that of peak change in the heart rate was smaller under the former than the latter (−49 ± 8 vs −63 ± 5 beats/min, respectively). Pretreatment of the animals under urethane-anesthesia with the selective IKs blocker chromanol 293B (n = 6) increased the extent of the dl-sotalol-induced QT interval prolongation to +57 ± 8 ms, which was only 0.56 times of that under the halothane-anesthesia, whereas the pretreatment increased the peak change in the heart rate to −76 ± 12 ms. These results indicate that the halothane-anesthesia may effectively sensitize the guinea-pig heart to pharmacological IKr blockade. Keywords:: QT interval prolongation, sotalol, halothane, urethane